Failures in agricultural innovation due to poor understanding of farmers' predispositions. Issue 5 (4th July 2018) - Razanakoto, Onjaherilanto; Razafindraibe, Rolland; Andriamananjara, Andry; Razafimanantsoa, Marie-Paule; Rakotoson, Tovohery; Smolders, Erik; Rabeharisoa, Lilia
ABSTRACT: Development projects in Madagascar have increased and evolved for half a century, yet they have failed to enhance farmers' performances. Related literature attributes the causes of failure as external to the project instigators, who are mostly institutions and funders. This article aims to highlight the role of development agents and their responsibility in unsuccessful projects. Participant observation of participatory learning and action research conducted in the Malagasy highlands revealed that non-consideration of the target audience's rationale makes the innovation processes provided by development projects obsolete.